PSYCHOTIC SYMPTOMS AS A RESULT OF CLOZAPINE INTOXICATION - Misheva, Aleksandra; Sotiroski, Petar; Babinkostova, Zoja; Manusheva, Nensi (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Clozapine intoxication can be a life-threatening condition because the drug is metabolized to Norclozapine, which is an active metabolite and can contribute to side effects. This is a case report of a 29-year-old female patient, who has been treated at a psychiatric clinic for 10 years due to PAS and alcohol abuse. Due to the appearance and persistence of auditory perceptual deceptions and delusional ideas, treatment with an atypical antipsychotic - clozapine in low doses (3 x 25 mg) was started. The current admission to a psychiatry clinic follows hospitalization at a toxicology clinic due to attempted suicide (TS) with 100 tablets of Clozapine 25 mg. The patient was admitted to a psychiatry clinic due to the persistence of psychotic symptomatology with visual hallucinations and paranoid ideas. After a determined interaction of the applied drugs with intensive monitoring of the condition, a reduction of the psychopathological content was followed without the application of additional therapy and proper treatment of her psychotic state was introduced.   Keywords: intoxication, clozapine, hallucinations, pharmacokinetics, pharmacodynamics